Ambientes virtuais de aprendizagem colaborativa e sua contribuição para o ensino de ciências - Pacheco, Rafael Scheffer (2017)
The present work describes an investigation that evaluated the use of collaborative learning virtual environments in the construction of knowledge about environmental education in a group of students of a public school of education. The virtual environment used was provided by Microsoft® on the OneDrive® platform. Sixteen students from a public school in Rio Grande do Sul participated in a pedagogical practice mediated by the collaborative virtual environment and answered a semi-structured interview, and the answers were submitted to the Discursive Textual Analysis, based on Moraes and Galiazzi (2007). After analyzing the data, two main categories emerged: I) Use of information and communication technologies in the teaching process. II) Building knowledge about the environment through collaborative virtual environments. Participants identified several contributions provided by the use of the virtual environment and the use of technology in school. The pedagogical proposal was developed from a learning unit, where the learning process was organized. The work developed used the principle of education through research, because it develops throughout a process that implies interaction with the sources of consultation and with the work group, opening the possibility of the emergence of new understandings.